Visionary leadership : creating a compelling sense of direction for your organization - Nanus, Burt. 4 0 16; 5 (San Francisco, California : Jossey-Bass Publishers, 1992)
Explores leadership, shows how vision is the key to leadership, and demonstrates how any leader can use a logical process to create a sense of direction.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Leadership. -- 20; 20; 2